1975
DOI: 10.1145/321906.321918
|View full text |Cite
|
Sign up to set email alerts
|

The Fanout Structure of Switching Functions

Abstract: The problem of determining the amount of fanout required to reahze a switching function m investigated. The significance of fanout in switching networks is discussed Fanout-free functions are introduced and their propertms examined. Two relations, adjacency and masking, are defined on the variables X of a functlonf(X), and these relations are used to characterize fanoutfree functions A quantity r(f) called the input fanout index of f is defined for arbitrary switching functions; r (f) represents the minimum nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0

Year Published

1978
1978
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 4 publications
(9 reference statements)
1
24
0
Order By: Relevance
“…DEFINITION 1 (Read-Once Function [17]). A Boolean formula φ is read-once if there exists a factorization such that each variable appears not more than once.…”
Section: Read-once Functions; Definitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…DEFINITION 1 (Read-Once Function [17]). A Boolean formula φ is read-once if there exists a factorization such that each variable appears not more than once.…”
Section: Read-once Functions; Definitionsmentioning
confidence: 99%
“…It is well known that in probabilistic databases with independent tuples, every result tuple is associated with a Boolean formula [3,13] (often called lineage), and the query evaluation problem reduces to computing the marginal probabilities for the result tuple Boolean formulas holding true. Further, if a result tuple's Boolean formula can be factorized into a form where every Boolean variable appears at most once, also known as read-once functions [15,17], then the marginal probability can be computed easily in linear time. Hierarchical queries always admit a query evaluation plan such that the result tuple formulas are generated in read-once form, thus providing a connection to efficient query evaluation in probabilistic databases.…”
Section: Introductionmentioning
confidence: 99%
“…The above questions have been answered for more restricted sets of modules in the literature. Hayes [8], [9] answers questions 1) and 2) for AND, OR, and NOT, while Chakrabarti and Kolp [6] answer the same questions for arbitrary two input modules which is equivalent to considering AND, OR, NOT, and EXOR. Butler [5] gives counting formulas for functions of arbitrary two input modules.…”
mentioning
confidence: 99%
“…Hence, the function h = x G® X2 ® -.0-x. can be factored out ofvarious terms in (3) with the consequent decomposition f = g(h(xl, m xm), x.+ *--Xn,)* Hayes [8] has shown that a necessary and sufficient condition forfto have a decomposition of the form (2) with (3) where the summation operation is EXCLUSIVE-OR, ij's are either 0 or 1, such that i is the decimal equivalent of the binary number in" 2 il, and xij = 1 ifij = 0 and xii = xiif i = 1. Then where df/dx1 = df/dx2 = X3 X4.…”
mentioning
confidence: 99%
See 1 more Smart Citation